2014
DOI: 10.1089/jmf.2013.0190
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Extend the Lifespan of MaleDrosophila melanogasterWhile Impairing Reproductive Fitness

Abstract: Green tea is a popular beverage believed to have many health benefits, including a reduction in the risks of heart disease and cancer. Rich in polyphenolic compounds known as catechins, green tea and its components have been shown to increase the lifespan of various animal models, including Drosophila melanogaster. Here, we investigated the genderspecific effects of green tea on the lifespan of fruit flies and observed that green tea extended the lifespan of male flies only. This effect was found to be indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 56 publications
6
40
1
Order By: Relevance
“…Green tea’s inability to protect against superoxide free radicals could be due to a higher dose of GTP resulting in green tea’s pro-oxidant toxic effect (Forester & Lambert, 2011). Some of our results may appear to disagree with our previous work where we did not observe protective effects against desiccation, and GTP did not increase water content (Lopez et al, 2014). The reason for this discrepancy is likely due to feeding GTP to adult flies in our previous work versus exposing embryos to GTP in this work.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Green tea’s inability to protect against superoxide free radicals could be due to a higher dose of GTP resulting in green tea’s pro-oxidant toxic effect (Forester & Lambert, 2011). Some of our results may appear to disagree with our previous work where we did not observe protective effects against desiccation, and GTP did not increase water content (Lopez et al, 2014). The reason for this discrepancy is likely due to feeding GTP to adult flies in our previous work versus exposing embryos to GTP in this work.…”
Section: Discussioncontrasting
confidence: 99%
“…While such toxicities have been cited in a number of reports, they are often over-looked, and their mechanisms are not fully understood. In line with some of these observations, we have previously reported that while green tea polyphenols (GTP) increased the lifespan of Drosophila melanogaster , it resulted in a reduction in male fertility (Lopez et al, 2014). …”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Any of which could possibly confer a lifespan extension. We have already found such a relationship in green tea, where lifespan extension is associated with decreased fertility in males (Lopez et al 2014). We are currently examining the effect of cinnamon and other botanicals on these other aspects of reproduction.…”
Section: Discussionmentioning
confidence: 56%
“…Evidence from in vitro and in vivo studies indicate that phytochemicals such as flavonoids, proanthocyanidins and anthocyanins (Long et al 2009;Dong et al 2012;Lopez et al 2014) can improve lifespan and delay the aging process. Besides the beneficial effects of plant preparations traditionally used by human population, double-sided properties of plant extracts have been verified.…”
Section: Discussionmentioning
confidence: 99%